The Harmony in the Text of the Brutal Wedding Play by Falah Shaker - طالب هاشم بدن (Basrah Arts Journal, 2022)
The study deals essentially with intertexuality of novels and its impact on the play “The Brutal dramatic art. It concerns intertexuality in Falah Shaker’s Wedding” of the novel by the French author (Jan Kivelik). In the first part, the work presents intertextuality and its effect on dramatic text. It shows the significance of studying intertextuality and its importance for whoever studies or concerns such subjects .The work reveals a set of terms that linguistically and idiomatically deals with intertextuality. In the second part, the work is subdivided into two sections, the first section deals with the concept of intertextuality and those who have dealt with subjects of intertextuality in ,to intertextuality in literature and linguistics , in addition dramatic art. The second section deals with intertextuality in the Western and Arab world, and how authors use it in dramatic art. The work shows some dramatic works that have been taken of other literary works such as poetry, novel, and other subjects in literature, the methods of intertuextulity and how a new text has been created of an old one. In the third part, the work presents an application of the process of intertextualization of the play that has been taken of Kivilik’s novel “The Brutal Wedding”. In the fourth part, the work shows the results, list of references that have supported and reinforced the study